Third nerve palsy as first presenting symptom of Guillain-Barre Syndrome spectrum clinical variant - Uma L. Balakrishnan; Nilesh K. Desai; Kimberly G. Yen (American Journal of Ophthalmology Case Reports)
Purpose: To report an unusual presentation of a Guillain-Barre Syndrome (GBS) spectrum clinical variant with an initial isolated, unilateral third nerve palsy prior to development of areflexia and lower extremity weakness. Observations: A 16-month-old presented with a pupil-involving right third nerve palsy and normal lower extremity strength and reflexes. She was treated with a short oral steroid taper for presumed post-infectious cranial nerve (CN) palsy and had initial improvement. Soon after completing the taper, she developed an inability to sit, stand, or crawl with lower extremity areflexia. Magnetic resonance imaging of the spine showed diffusely thickened and enhancing cauda equina nerve roots and lumbar puncture showed isolated elevated protein, consistent with a diagnosis of a GBS spectrum disorder. She was treated with intravenous immunoglobulin and had complete resolution of ptosis as well as normal extraocular movements. Conclusions and importance: Pediatric cases of acute third nerve palsy are most often traumatic, neoplastic, vascular, or demyelinating. These cases are less likely to have a post-viral etiology in contrast to the more commonly encountered acquired sixth nerve palsy. An isolated, unilateral third nerve palsy is a rare presentation of GBS and its clinical variant Miller Fisher Syndrome. This case demonstrates the importance of a high level of suspicion, particularly in the context of worsening systemic symptoms, to include these demyelinating disorders as a possible cause of unilateral CN palsy, as they can have a good prognosis if treated appropriately.